Carcass and cut yields and meat qualitative traits of broilers fed diets containing probiotics and prebiotics - Pelicano,ERL (2005)
This study evaluated the use of different probiotics, prebiotics and symbiotics on the quality of carcasses and meat of broiler chickens. One hundred and eight day-old Cobb male broilers were used (n=108) in a completely randomized design according to a 3x3 factorial, with 3 probiotics in the diet (no probiotics, probiotics 1, probiotics 2) and 3 prebiotics in the diet (no prebiotics, prebiotics 1, prebiotics 2). There were nine treatments with 4 replicates and 3 birds per replicate. The results showed that the carcass and cut yields, color (L* - lightness, a* - redness, and b* - yellowness), pH, cooking losses, shearing force and sensory analysis were not affected by the use of different growth promoters at 42 days of age. It was concluded that growth promoters supplemented to the diet did not affect the studied quantitative and qualitative parameters of the carcass and breast meat of broiler chickens.